FAKTOR-FAKTOR YANG MEMPENGARUHI KESEMPATAN KERJA DI PROVINSI BANTEN TAHUN 2010-2019 - Teguh Fajar Saputra; Dijan Rajuni; Sukiman Sukiman (FEB Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to examine the effect of variable government spending, number of companies, foreign investment, and domestic investment on employment opportunities in Banten Province and to determine the most influential variables. Banten Province in 2018 was the province with the lowest employment opportunity rate in Indonesia. This study uses a panel data model with a fixed-effect model (FEM) for 8 districts/cities from 2010 to 2019 and elasticity analysis to determine the most influential variables. The results showed that the variable government spending, the number of companies, and domestic investment had a positive and significant effect on the job opportunity variable, while the foreign investment variable did not affect. The number of companies variable is the most influential variable. The implication is that to increase employment opportunities the government can increase government spending, encourage the creation of new company units, and increase domestic investment.